A chromosome‐scale assembly of the bilberry genome identifies a complex locus controlling berry anthocyanin composition. (4th August 2021) - Wu, Chen; Deng, Cecilia; Hilario, Elena; Albert, Nick W.; Lafferty, Declan; Grierson, Ella R. P.; Plunkett, Blue J.; Elborough, Caitlin; Saei, Ali; Günther, Catrin S.; Ireland, Hilary; Yocca, Alan; et al.
Abstract: Bilberry ( Vaccinium myrtillus L.) belongs to the Vaccinium genus, which includes blueberries ( Vaccinium spp.) and cranberry ( V . macrocarpon ). Unlike its cultivated relatives, bilberry remains largely undomesticated, with berry harvesting almost entirely from the wild. As such, it represents an ideal target for genomic analysis, providing comparisons with the domesticated Vaccinium species. Bilberry is prized for its taste and health properties and has provided essential nutrition for Northern European indigenous populations. It contains high concentrations of phytonutrients, with perhaps the most important being the purple colored anthocyanins, found in both skin and flesh. Here, we present the first bilberry genome assembly, comprising 12 pseudochromosomes assembled using Oxford Nanopore (ONT) and Hi‐C Technologies. The pseudochromosomes represent 96.6% complete BUSCO genes with an assessed LAI score of 16.3, showing a high conservation of synteny against the blueberry genome. Kmer analysis showed an unusual third peak, indicating the sequenced samples may have been from two individuals. The alternate alleles were purged so that the final assembly represents only one haplotype. A total of 36, 404 genes were annotated after nearly 48% of the assembly was masked to remove repeats. To illustrate the genome quality, we describe the complex MYBA locus, and identify the key regulating MYB genes that determine anthocyanin production. The new bilberry genome builds on the genomic resources and knowledge of Vaccinium species, to help understand the genetics underpinning some of the quality attributes that breeding programs aspire to improve. The high conservation of synteny between bilberry and blueberry genomes means that comparative genome mapping can be applied to transfer knowledge about marker‐trait association between these two species, as the loci involved in key characters are orthologous.